Recurrent leiomyosarcoma with de-differentiation to chondrosarcoma and osteosarcoma: a case report - Summers, Zara; Melloy, Aemelia; Jeyarajan, Eshwarshanker; Wills, Timothy; Parker, David; Rutherford, Leigh; Townend, Philip (International Surgery Journal, 2021)
Leiomyosarcoma are a rare type of tumour of smooth muscle that can be found in the retroperitoneum. There is a paucity of reported data around dedifferentiation of leiomyosarcoma. Our case report describes de-differentiation of recurrent leiomyosarcoma into osteosarcoma and chondrosarcoma in a patient who had a local recurrence of his leiomyosarcoma. The recurrence is on a background of intermediate grade leiomyosarcoma of the retroperitoneum and he underwent his original resection in 2019 and included a right nephrectomy and right hemicolectomy. Our patient is currently undergoing radiotherapy and we will continue ongoing follow up for his progress.